Evaluación de Carga Mental y Fatiga Física en los trabajadores del Cuerpo de Bomberos Guaranda en el período 2024 - Rea Toalombo, Jairo Maximiliano (2025)
This research deals with the analysis of the mental load and physical fatigue that occur due to unfavorable work conditions such as long hours, overload, role ambiguity, among other aspects of the labor sectors. The objective of the work is to evaluate and measure the different levels of mental load and physical fatigue of the workers of the Guaranda Fire Department. The type and design of the research was descriptive, non-experimental, transversal and correlational between the sociodemographic variables and the levels of Mental Load detected by the Swat test and the Yoshitake test to determine Physical Fatigue. The study population was 17 Operational Firefighters and 13 were administrative personnel who answered the applied tests. Reliability and reliability were determined through Crombach's Alpha and KMO through a pilot test. The results obtained from Mental Load: 86.7% medium and 13.3% high; Regarding Physical Fatigue: 73.3% Low and 26.7% medium. By detecting cases of both Mental Burden and Physical Fatigue with high average values as a psychosocial risk factor, it is concluded that preventive measures should be implemented based on a Positive Psychology manual that helps mitigate their negative effects on the health of the Guaranda Firefighters personnel.